MARKETING STRATEGIES IN INCREASING THE SALES VOLUME OF MANGAMBANG 575 AGROTOURISM, LAU SUB-DISTRICT, MAROS DISTRICT - Nurul Amalia (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research aims to find out the marketing strategies used by Mangambang agro-tourism owners in increasing sales volume. The type of research conducted is using a qualitative descriptive approach. The types and sources of data used are primary data and secondary data, while data collection techniques are carried out by means of interviews, observation and documentation. Data analysis used in this research consists of several stages, namely data reduction and presentation stages and the conclusion drawing stage. The results of this research are: 1) Products in mini markets that provide snacks and fishing equipment, then cafes and restaurants that provide food and beverage menus. Price, the price set follows the standard method by adding a certain percentage of the base price of distributors and raw materials. Then Place (distribution channel), the distribution channel used by Mangambang 575 agrotourism is on the main road of Marannu village, access to this place is quite easy because the distance is only about 900 metres from the Maros-Pangkep axis road. next Promotion, Mangambang 575 uses offline and online promotions to market its products. Offline applies a special strategy where information about the products in Mangambang 575 is spread from customer to customer. This means that customers who are satisfied with Mangambang 575's service and menus will provide information about the product to others. Through online, by providing information and reviews of consumers and visitors on social media. 2) Mangambang 575's sales volume has decreased, sales turnover in 2020-2022 for sales per day reached IDR 8,000,000. But in contrast to the years 2023-2024, the sales turnover per day experienced a significant decline, only in the range of 1,500,000-3,000,000 rupiah. The decrease in turnover was caused by increasingly fierce price competition and the increasing number of tours or agro-tourism. However, from the strategies that have been implemented, Mangambang 575 has been able to restore high sales turnover even though it is not the same as the sales turnover in the past few years.